CpG demethylation in the neurotoxicity of 1-methyl-4-phenylpyridinium might mediate transcriptional up-regulation of α-synuclein in SH-SY5Y cells. (17th October 2017) - Yang, Jian; Yang, Zhaofei; Wang, Xuan; Sun, Min; Wang, Yong; Wang, Xiaomin
Graphical abstract: Highlights: Neurotoxin MPP + induces CpG demethylation in neuronal cells. CpG demethylation mediates transcriptional up-regulation of α-synuclein in neurotoxicity. DNA methyltransferases (DNMTs) contribute to CpG demethylation of the α-synuclein promoter in neurotoxicity. Abstract: The accumulation of α-synuclein is the primary pathological hallmark of Parkinson's disease (PD). In PD patients, CpG demethylation of intron-1 has been reported to be associated with α-synuclein up-regulation. Environmental factor, for example neurotoxin, is a major etiological risk factor in PD pathogenesis. However, the role of CpG methylation in neurotoxin-induced PD has not been addressed completely yet. To explore CpG methylation associating with α-synuclein transcription and its underlying mechanisms in the neurotoxin-induced PD pathology, human neuroblastoma SH-SY5Y cells were treated with neurotoxins 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenylpyridinium (MPP + ). Results showed that MPP + induced demethylation of the whole length of the CpG island around SNCA promoter, and both 6-OHDA and MPP + resulted in up-regulation of SNCA transcription. The CpG demethylation around promoter resulted in up-regulation of SNCA transcriptional activity. In addition, 6-OHDA and MPP + induced the reduced levels of DNA methyltransferase (DNMT) 3a and DNMT3b but not DNMT1. These data suggested that CpG demethylation was induced by MPP + and might mediate up-regulation of SNCA transcription in neurotoxin-induced PD. And down-regulation of both DNMT3a and DNMT3b, but not DNMT1, might contribute to CpG demethylation of the SNCA promoter.